Identification of fundamental principles behind the treatment of skin diseases with acupuncture using network analysis - Heeyoung Moon
Acupuncture has been used to treat various skin disorders, such as dermatitis, psoriasis, acne, and rash. Local acupoints close to the site of symptoms, distant acupoints along the meridian, and distant acupoints thought to have a particular characteristic to treat skin symptoms are assumed to be effective for treating pain diseases. However, there is still no known acupoint combination principle for the treatment of dermatological conditions. We aimed to provide an overview of networks of acupoints used to treat skin diseases and symptoms. We reviewed and analyzed acupoints in two classical literatures, "Chim-Gu-Kyung-Heom-Bang" (CGKHB) and "Sa-am-doin-chim-beub" (SDCB). With the help of network parameters (degree and centrality) and clusters identified by the network analysis, we characterized the principles of acupuncture treatment for skin diseases. While acupoints of CGKHB had a clustering pattern similar to the pattern of symptoms (i.e., causes and features of skin symptoms) rather than the location of symptoms, the acupoints of SDCB displayed a clustering pattern primarily based on the location of symptoms (i.e., where symptoms are present). The findings indicate that one acupuncture style used in CGKHB places an emphasis on disease symptoms, while another style used in SDCB is more focused on the locations of skin symptoms in order to locate acupoints for skin diseases. Our research will help researchers better understand acupuncture treatment strategy in dermatology. Further research is required to determine how traditional theories can benefit clinical practice and we need to develop an evidence-based clinical practice guideline for acupuncture in dermatology.